A produção imobiliária de loteamentos residenciais e o poder das elites locais : os casos de Colatina e Linhares/ES - Assis, Leandro Camatta de (2022)
The real estate production has focused on the building of housing subdivisions in the last 20 years in Colatina and Linhares, which are municipalities in the north of Espírito Santo state, is the object of investigation of this work. As a consequence of the implementation of residential subdivisions by construction companies and real estate developers, there is an expansion of horizontal urban growth, which contributes to the formation of a discontinuous and dispersed peripheral pattern of these cities. The peripheral pattern once attributed as a space for a less favored population, deprived of the minimum conditions of infrastructure and decent housing, was responsible for the ills of the physical, social and economic deterioration of cities (BOLAFFI, 1982). Today, it appears that this growth pattern is repeated. Yet, it was established by the formal production of space, through subdivisions that, besides extanding the urban perimeter of cities in a discontinuous way, expel the population with lower purchasing power to even more distant spaces. Hence, the objective of the research was to understand the real estate production of residential subdivisions in the process of urban growth with a peripheral character. Real estate production is understood here as the formal production of subdivisions that instrumentalize the use of land, making it function as a commodity and then establishing a new form for capital accumulation. As land is a natural asset not produced by man, the appreciation of the capital in the production of subdivisions creates a growing demand for land, forcing the permanent expansion of the urban perimeter of cities. Therefore, through interviews with agents of the production of space, the analysis of data on the production of subdivisions and the bibliographic references relevant to the subject in question, it was possible to analyze the overlapping of the exchange value of the space in relation to its use value and then, understanding how capital transforms space into merchandise through the instrumentalization and commodification of land, with destructive consequences for the population. Futhermore, it was possible to show that local elites contribute preponderantly to the production of new urban areas and the expansion of the city's fabric, since they articulate a powerful network of influence over local authorities, which produce laws and infrastructure to guarantee the reproduction of capital in real estate activity. Finally, it is observed that urban living is transformed as it is set by a logic that is established for accumulation and that expands the limits of the city, expelling the poor population to more distant and precarious locations.